Health facility-based prevalence of typhoid fever, typhus and malaria among individuals suspected of acute febrile illnesses in Southwest Region, Ethiopia - Abayneh, Mengistu; Aberad, Mitiku; Habtemariam, Yosef; Alemu, Yared (Frontiers in Epidemiology, 2024)
Background: Acute febrile illnesses such as typhoid fever, typhus, and malaria are still major causes of hospital admission in many parts of Ethiopia. However, there are substantial gaps in the monitoring systems, which result in a lack of knowledge about the geographic distribution and role of common pathogens, particularly in rural areas. Thus, this study was aimed at assessing the seroprevalence of typhoid fever, typhus, and malaria among suspected acute febrile patients at the MTU Teaching Hospital and Mizan-Aman Health Center, Southwest region of Ethiopia.Method: A health facility-based cross-sectional study was carried out from July to October 2022. Blood samples were collected from a total of 384 individuals. Widal and Weilfelix direct card agglutination and tube agglutination test methods were used for the Salmonella enterica serotype Typhi (S. typhi) and Rickettsia infections. The diagnosis of malaria was made using thick and thin blood smears. Questionnaires given by interviewers were used to gather information on risk factors and other sociodemographic factors. The data was analyzed using STATA/SE 14.0.Result: A total of 371 patients were tested for S. Typhi and Rickettsia infections using direct card agglutination and tube agglutination methods. Using the screening test, 20.5% (76/371) patients were reactive either for O or H antigens or both, of which 55.3% (42/76) were reactive by the titration test at the cutoff value ≥ 1:80. About 17.5% (65/371) were reactive to OX19 antigen by card agglutination test, and of which 58.5% (38/65) were reactive by the titration test at the cutoff value ≥ 1:80. The overall seroprevalence of S. Typhi and Rickettsia infections using combined direct card and tube agglutination techniques was 11.3% (42/371) and 10.2% (38/371), respectively. Out of 384 suspected malaria patients, 43 (11.2%) were found positive either for P. falciparum, 27 (7.03%), or P. vivax, 16 (4.2%).In this study, typhoid fever, typhus, and malaria were found among symptomatic acute febrile patients. To increase disease awareness, it is necessary to provide sustainable health education about risk factor behaviors, disease transmission, and prevention strategies. In addition, improving laboratory diagnosis services and early treatment may also lower the likelihood of potentially fatal consequences.